PENGARUH INFORMASI DAN MEDIA EDUKASI DALAM MENDUKUNG MANAJEMEN DIRI PENDERITA DIABETES MELITUS DI RSU ROYAL PRIMA MEDAN - Juli Elisabet Mayen br Meliala; Albert Albert; Santy Deasy Siregar; Ermi Girsang (Postgraduate, University of Mataram, 2023)
The purpose of this study is to determine the effect the need for information and educational media in supporting self-management of people with diabetes mellitusat RSU Royal Prima Medan. This type of research is a quantitative research with a cross sectional approach. The population in this study isout patient diabetes mellitusat RSU Royal Prima Medan from January 2022 to December 2022 who have been diagnosed based on criteria totaling 548 patients. Sampling used the Taro Yamane formula with a total sample of 100 samples. Data analysis in this study used univariate analysis and bivariate analysis. The research results show that the majority of diabetes mellitus patients in this study were aged 31-40 years and the majority of patients were male, the quality of self-management of people with diabetes mellitus at RSU Royal Prima Medan was good for 89 patients and 11 patients who were not good, Information needs play a role and influence in supporting self-management of people with diabetes mellitus at RSU Royal Prima Medan p value <0.05, educational media play a role and influence in supporting self-management of people with diabetes mellitus at RSU Royal Prima Medan p value <0.05. Suggestions for RSU Royal Prima Medan should be to maximize all forms of educational activities as well as information regarding self-management of people with diabetes mellitus, such as routinely giving seminars to people with diabetes mellitus on how to maintain good self-management for people with diabetes mellitus